The Impact of the war Between Russia and Ukraine on Trade Routes in the Black Sea - Wija Anarki Andi Cella; Seniwati Seniwati (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This paper explores the difficulties of unblocking the operations of Black Sea ports that remain under Ukrainian control, as well as the geopolitical dynamics between Russia and Ukraine in the area. There are two primary obstacles: first, Ukraine must preserve its coastal defense capabilities against the threat of Russian invasion without undermining the security of its land; second, it is crucial to ensure that Russia adheres to the regulations that safeguard freedom of navigation in the Black Sea. Since Russia's annexation of Crimea in 2014, Russia's influence in the Sea of Azov and the Black Sea has expanded, jeopardizing the security interests of Ukraine as well as Western partners, such as the US and NATO. The analysis suggests measures that NATO and other allies can implement to enhance maritime security in the region, including bolstering Ukraine's navy and augmenting NATO's presence in the Black Sea. This dispute not only impacts relations between Ukraine and Russia, but also influences regional political and security stability in Southeastern Europe as well as broader international diplomacy.